Key effects on the confinement improvement of the ASDEX Upgrade hybrid scenario. (9th September 2019) - Jian, Xiang; Chan, Vincent S.; Chen, Jiale; Bock, Alexander; Zohm, Hartmut; Fable, Emiliano; Reisner, Maximilian; Guo, Wenfeng; Zhuang, Ge
Abstract: Transport analysis of a fully non-inductive high performance ASDEX Upgrade (AUG) hybrid mode discharge (Bock 2017 Nucl. Fusion 57 126041) is performed using a gyro-fluid transport code and a gyro-kinetic stability code. It is shown that the confluence of several mechanisms is essential for the improvement in core confinement. In addition to rotation shear, low magnetic shear, which is a common characteristic near the magnetic axis of a hybrid scenario, is found to be favorable for both electromagnetic and α stabilization. Together they facilitate the conditions for fast ions to establish a strong local internal transport barrier by providing additional dilution effect and enhancement of α stabilization. This study provides a complete picture and demonstrates that a quasilinear turbulent model is capable of quantitatively matching the experimental temperature profiles across the entire core of a hybrid mode discharge.